2002
DOI: 10.1016/s0378-1097(02)01042-x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and identification of cysteine desulfhydrase of Corynebacterium glutamicum, and its relationship to cysteine production

Abstract: We highly purified the enzyme having L-cysteine desulfhydrase activity from Corynebacterium glutamicum. According to its partial amino acid sequence, the enzyme was identified as the aecD gene product, a C-S lyase with K, L-elimination activity [I. Rossol and A. Pu «hler (1992) J. Bacteriol. 174, 2968^2977]. To produce L-cysteine in C. glutamicum, the Escherichia coli-altered cysE gene encoding Met256Ile mutant serine acetyltransferase, which is desensitized to feedback inhibition by L-cysteine, was introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…With cystathionine and L-cystine, the control exhibited comparable specific activities of 0.13 and 0.11 mol min Ϫ1 mg Ϫ1 , respectively. With metC overexpressed, the specific activities were increased to , corroborating the finding that cystathionine ␤-lyase has L-cysteine desulfhydration activity (59). Also with L-serine a significant activity of 0.04 Ϯ 0.01 mol min Ϫ1 mg…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…With cystathionine and L-cystine, the control exhibited comparable specific activities of 0.13 and 0.11 mol min Ϫ1 mg Ϫ1 , respectively. With metC overexpressed, the specific activities were increased to , corroborating the finding that cystathionine ␤-lyase has L-cysteine desulfhydration activity (59). Also with L-serine a significant activity of 0.04 Ϯ 0.01 mol min Ϫ1 mg…”
Section: Resultssupporting
confidence: 71%
“…With the others, a correlation to L-serine is probably less apparent (see Discussion). Most interestingly, the cystathionine ␤-lyase mRNA level (metC) is increased 2.4-fold, and the respective enzyme of L-methionine synthesis (24), catalyzing a ␤-elimination reaction, has been reported to have a broad substrate specificity in C. glutamicum and in E. coli, also reacting with L-cysteine, which is structurally related to L-serine (1,45,59).…”
Section: Resultsmentioning
confidence: 99%
“…1) In our previous study, we found cysteine production by C. glutamicum having an altered E. coli serine acetyltransferase gene. 2) The whole-genome sequencing project was completed in 2002, 3) and two cysteine biosynthetic genes, cysE and cysK, are registered in the data base as the genes encoding putative serine acetyltransferase and O-acetylserine sulfhydrylase (OASS), respectively (accession no. AX405283).…”
mentioning
confidence: 99%
“…When necessary, kanamycin (50 g/ml) was added to the medium. Plasmid pVK7, 2) which can replicate and express the bacterial kanamycin resistant gene in B. lactofermentum, C. glutamicum, and E. coli, was used to express the cysK gene encoding for OASS in C. glutamicum.…”
mentioning
confidence: 99%
“…Plasmid pVK7, which can replicate and express the bacterial kanamycin-resistant gene in Brevibacterium lactofermentum, C. glutamicum, and E. coli, 24) was used to express the ilvBNC gene encoding AHAS and AHAIR. To obtain the complete coding sequence including its promoter region for the ilvBN gene and the sequence for ilvBN that was truncated at the 3 0 region of the ilvN gene, PCR amplification was performed.…”
Section: )mentioning
confidence: 99%